Microbe-mediated regulation in zinc-contaminated soils: the synergistic role of hyperaccumulator plants and zinc-tolerant rhizobacteria - Rani, Nitu; Chauhan, Arjun; Sagar, Narashans Alok; Kumar, Vinay (Frontiers in Agronomy, 2025)
Zinc (Zn) contamination in soils is a serious environmental issue with adverse impacts on plant growth and crop productivity. High concentrations of Zn can induce toxicity in plants, leading to reduced growth, impaired nutrient uptake, and oxidative stress. However, some plants can resist and even collect Zn in their tissues, known as hyperaccumulators. Further, the utilization of rhizobacteria as a sustainable approach for mitigating Zn stress in plants and remediating Zn-contaminated soils has gained significant attention. The use of these hyperaccumulator plants and rhizobacteria can help overcome soil Zn contamination and improve soil fertility through phytostabilization, phytoextraction, and phytomining. Furthermore, the ability of rhizobacteria to enhance plant growth, alleviate Zn toxicity symptoms, and improve nutrient uptake efficiency makes them valuable allies in sustainable agriculture and soil remediation practices. The present review provides insights into the sources and impacts of Zn contamination, the noxious effects on plants, the mechanism of Zn hyperaccumulator plants, and the potential of rhizobacteria in alleviating Zn stress and remediating Zn contaminated soils.